Treatment of chronic rhinosinusitis with nasal polyposis with oral steroids followed by topical steroids: a randomized trial. - Vaidyanathan S; Barnes M; Williamson P; Hopkinson P; Donnan PT; Lipworth B; Vaidyanathan, Sriram; Barnes, Martyn; Williamson, Peter; Hopkinson, Pippa; Donnan, Peter T; Lipworth, Brian (Annals of Internal Medicine, 2011)
Background: Chronic rhinosinusitis (CRS) with nasal polyposis is common. The long-term efficacy and safety of approaches to medical management are not well-known.Objective: To evaluate the efficacy and safety of a 2-week regimen of oral steroid therapy followed by 26 weeks of sequential topical steroid maintenance therapy.Design: Parallel randomized trial with computer-generated block randomization and central allocation. Patients and investigators were blinded to group assignment. (ClinicalTrials.gov registration number: NCT00788749)Setting: A specialty rhinology clinic in Tayside, Scotland.Patients: 60 adults with CRS and moderate-sized or larger nasal polyps who were referred by their primary physicians for specialty care.Interventions: Patients were randomly assigned in a 1:1 ratio to receive oral prednisolone, 25 mg/d, or placebo for 2 weeks, followed in both groups by fluticasone propionate nasal drops, 400 µg twice daily, for 8 weeks and then fluticasone propionate nasal spray, 200 µg twice daily, for 18 weeks.Measurements: Polyp grading (primary outcome), hyposmia score, quality of life, symptoms, nasal patency, adrenal function, and bone turnover.Results: The mean decrease in polyp grade from baseline to 2 weeks was 2.1 units (SD, 1.1) in the prednisolone group and 0.1 unit (SD, 1.0) in the placebo group (mean difference between groups, -1.8 units [95% CI, -2.4 to -1.2 units]; P < 0.001). The difference between groups was -1.08 units (CI, -1.74 to -0.42 unit; P = 0.001) at 10 weeks and -0.8 unit (CI, -1.8 to 0.2 unit; P = 0.11) at 28 weeks. The mean decrease in hyposmia score from baseline to 2 weeks was 31.12 mm (SD, 30.1) in the prednisolone group and 1.41 mm (SD, 30.6) in the placebo group (mean difference between groups, -28.33 mm [CI, -42.71 to -13.96 mm]; P = 0.002). The difference between groups was -16.06 mm (CI, -30.99 to -1.13 mm; P = 0.03) at 10 weeks and -12.13 mm (CI, -30.55 to 6.29 mm; P = 0.19) at 28 weeks. Prednisolone therapy resulted in transient suppression of adrenal function and increase in bone turnover after 2 weeks, with a return to baseline at 10 and 28 weeks.Limitations: Patients were referred from primary care to a single-center rhinology clinic, which limits the generalizability of results. Serial measurements of surrogates of nasal inflammation (such as nitric oxide or cytokine levels) were not performed.Conclusion: Initial oral steroid therapy followed by topical steroid therapy seems to be more effective over 6 months than topical steroid therapy alone in decreasing polyp size and improving olfaction in patients referred for specialty care of CRS with at least moderate nasal polyposis.Primary Funding Source: Chief Scientist Office, Scotland; National Health Service Tayside Small Grants Scheme; and an Anonymous Trust grant from University of Dundee.